2005
DOI: 10.1116/1.1935530
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic metal etching with organic based plasmas. I. CO∕H2 plasmas

Abstract: The chemical processes within high-density CO∕H2 plasmas are examined using supersonic pulse, plasma sampling mass spectrometry. The principle chemistry observed is consistent with a Fischer–Tropsch process and results in the formation of primarily formic acid and a C2O2Hx species tentatively identified as ethenediol. The high-density plasmas used are shown to etch nickel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…5 Finally, shoulders appear on either side of m / z = 80, implying that this peak is more than simply Ar 2 . These are the remaining intensity of the ͑NH 3 ͒ 3 H + cluster that dominated the flow spectra.…”
Section: B Plasma Mass Spectramentioning
confidence: 98%
See 2 more Smart Citations
“…5 Finally, shoulders appear on either side of m / z = 80, implying that this peak is more than simply Ar 2 . These are the remaining intensity of the ͑NH 3 ͒ 3 H + cluster that dominated the flow spectra.…”
Section: B Plasma Mass Spectramentioning
confidence: 98%
“…In the CO/ H 2 investigation, 5 Fischer-Tropsch chemistry 15 was proposed as the source of the formic acid and enthanediol. In industrial Fischer-Tropsch processes, a mixture of hydrogen and carbon monoxide is reacted in the presence of an iron, cobalt, or nickel catalyst.…”
Section: B Plasma Mass Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, studies have shown that Cl-based plasmas are good candidates for metal etching. Organic plasma mixtures can etch some metals, by pure ion bombardment processes or, in some cases, by forming volatile organometallic compounds, with CH 4 or C 3 H 6 O plasmas for example [21][22][23].…”
Section: Literature Overviewmentioning
confidence: 99%